Building online communities with phpBB 2 - Stefanov, Stoyan; Rogers, Jeremy; Lothar, Mike.; Safari eBooks (Birmingham, U.K. : Packt Pub., 2005)
"This book gives you the power to use phpBB to set up and run your own online discussion forums with ease, and develop your own Internet community. It takes you through the whole process of setting up your phpBB site, and helps you create, customize and manage your own online community with phpBB. Written by experienced phpBB administrators and enthusiasts, the emphasis is on simple, and practical guidance for you to get the most from phpBB."--Resource description page.
Description based on print version record.
"A practical guide to creating and maintaining your own online discussion forums with phpBB, the leading free open-source PHP/MySQL-based bulletin board package."--Cover.
Includes index.
Keywords: Computer bulletin boards; PHP (Computer program language); SQL (Computer program language); Web site development; Web sites -- Design; Open source software; Electronic books